A critical analysis on the efficiency of property development approval processes in the City of Cape Town - Webster, Simon (School of Architecture, Planning and Geomatics, 2023)
The Western Cape Government Economic War Room has identified that land-use management in the City of Cape Town is inefficient. Coupled with the fact that there is a housing crisis within the City of Cape Town, it is imperative that such inefficiencies are addressed with urgency. Current development regulations in the City of Cape Town are said to be hindering the involvement of the private sector in the property development space and adding unnecessary delays to the property development sector in general. This paper will argue that a reason for this can be attributed to convoluted legislation linked to property development approval processes, that is being too rigidly interpreted and not administered efficiently. There is therefore a need to understand how the overall development application system is run, especially in relation to the land use and building plan application processes, to assist in identifying the inefficiencies affecting the property development space as a whole. This will allow pragmatic solutions to be formulated and expanded on, to better expound how a more efficient development environment can be created. A further important factor in better understanding the property development space, is comprehending the context within which it functions. Namely, the governance systems which affect it, the laws and regulations applicable to it, and the lack of emphasis on saving time throughout the application process. The purpose of this paper is to show where the inefficiencies lie in the land use management and building development management application processes, and why such inefficiencies may be happening. This paper will also discuss and recommend further topics that should be studied in order to resolve the various issues named. The methodology used to achieve the aforementioned was a mixed method of data collection, which encompassed various interviews with experts working within the property and planning development fields, iterative communication with these professionals, and literature reviews. In sum, there is no one answer to the identified issues as there are many interconnected complexities that must be dealt with in order to address the inefficiencies effectively. What is clear however, is that the current implementation of administrative penalties by the City of Cape Town are causing major capacity issues within the Development Management department and Municipal Planning Tribunal, and which ultimately has a ripple effect on the system as a whole.